2021
DOI: 10.1126/science.abe9728
|View full text |Cite
|
Sign up to set email alerts
|

Three-quarters attack rate of SARS-CoV-2 in the Brazilian Amazon during a largely unmitigated epidemic

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) spread rapidly in Manaus, the capital of Amazonas state in northern Brazil. The attack rate there is an estimate of the final size of the largely unmitigated epidemic that occurred in Manaus. We use a convenience sample of blood donors to show that by June 2020, 1 month after the epidemic peak in Manaus, 44% of the population had detectable immunoglobulin G (IgG) antibodies. Correcting for cases without a detectable antibody response and for antibody… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
473
2
20

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 474 publications
(523 citation statements)
references
References 39 publications
(19 reference statements)
28
473
2
20
Order By: Relevance
“…In the USA the prevalence of seropositivity was 19.1% in New York City in the month of April (30), and at the same time it was 4.65% in California (31). High seropositivity rates (respectively 22%, 42% and 66%) have been reported in April 2020 in Guilan, Iran and in July 2020 both in Bergamo, Italy and in Manaus, Brazil (32, 33, 34).…”
Section: Discussionmentioning
confidence: 99%
“…In the USA the prevalence of seropositivity was 19.1% in New York City in the month of April (30), and at the same time it was 4.65% in California (31). High seropositivity rates (respectively 22%, 42% and 66%) have been reported in April 2020 in Guilan, Iran and in July 2020 both in Bergamo, Italy and in Manaus, Brazil (32, 33, 34).…”
Section: Discussionmentioning
confidence: 99%
“…The rst lineage replacement started after the rst epidemic peak and was a gradual process of nearly ve months during which lineage B.1. A study of blood donors conducted in Manaus estimated that the rst wave of SARS-CoV-2 infected 76% (95% CI 67-98) of the city's population by October 2020, suggesting that herd immunity had already been reached 6 . Assuming that reinfection is rare and that immunity against infection did not signi cantly wane by December 2020, a second COVID-19 wave would not be expected so early.…”
Section: Discussionmentioning
confidence: 99%
“…The resurgence of cases in Manaus was described as follows: "from the second week of August there has been a small increase in the number of cases which, at the time of writing, has begun to decline (page 3)" (241). In addition, the peak seroprevalence in blood donors in Manaus was 51.8% in June, while another study of household seroprevalence in Manaus on May 14-21 found this to be 12.7% (the respective numbers for São Paulo were closer, at 6.9 and 3.3% in the two serosurveys) (241,242). Even correcting for a possible lower sensitivity of capillary blood used in the household survey does not explain the difference, as the corrected seroprevalence might be up to 19.3% (243).…”
Section: Content Of the Call For Adjusting Covid-19 Response Prioritiesmentioning
confidence: 92%
“…This also applies to a more recent review finding 17 cases of reinfection reported of whom 3 were hospitalized and the one died (238). Regarding Manaus, the high seroprevalence likely reflected the special situation of a relatively homogeneous cohort of people in overcrowded low socioeconomic urban situations, with reliance on crowded long riverboat travel; now there seems to be a different demographic cohort of young wealthy individuals being exposed (239)(240)(241). The resurgence of cases in Manaus was described as follows: "from the second week of August there has been a small increase in the number of cases which, at the time of writing, has begun to decline (page 3)" (241).…”
Section: Content Of the Call For Adjusting Covid-19 Response Prioritiesmentioning
confidence: 99%